Sustainability indicators in dairy livestock: systematic review (Research, Society and Development, 2022)
Dairy farming is an activity of great economic importance for Brazil, which uses natural resources as raw material, and inadequate management can harm the soil, contaminate water and harm the maintenance of biodiversity. the sustainability parameters of dairy farming that were surveyed using the ISA tool. A systematic review of the bibliography was carried out in the Web of Science, SciElo and Google Scholar databases, and the results found in ten articles were investigated in the parameters ' environmental sustainability indicators', 'water quality' and 'APPs'. It was concluded that, according to the results found in the properties analyzed, only one article conceptualized both parameters as excellent, leading to believe in the need for awareness of the owners and the creation of public policies aimed at preserving the environment due to the damage caused by the dairy farming activity.